An Efficient Synthesis of Hybrid Chalcone and Acetyl Pyrazoline Derivatives as Potent Antimycobacterial and Antimicrobial Agents: Development of Novel Antimicrobial Agents (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Due to increasing microbial drug resistance, it is to more necessary to develop new antimycobacterial and antimicrobial agents. For this purpose, some new indole base chalcone (Va-e) analogs synthesised and converted into 1-acetyl-2-yrazoline (VIa-e) derivatives.Target compounds were evaluated for their antimycobacterial efficacy against Mycobacterium tuberculosis H37Rv and antimicrobial activity against four common pathogenic bacterial and three common fungal strains. Structures of entire newly synthesized compounds were assigned on the basis of FTIR, 1H NMR, 13C NMR, LCMS as well as elemental analysis. Five derivatives (Va, Vd, Ve, VIb and VIc) displayed significant antitubercular activity. In terms of antimicrobial activity, most compounds exhibited moderate to potent activity against the bacteria and the fungal.